Anfíbios do Legado das Águas-Reserva Votorantim, SP - Lucas, Marcelo Stéfano Bellini (Universidade Federal de São Carlos, 2019)
The Atlantic Forest is one of the richest centers of global biodiversity and also the most threatened. Despite this, have an expressive biodiversity, with high rates of endemism, related to a variety of microhabitats. The great loss of original forest and intense forest fragmentation are mostly due to anthropogenic action, leaving only 8.5% of its original forest cover. The protection of the remaining forest is a responsibility of public and private Conservation Units (UCs) that are a refuge for the diversity of the biome. The Conservation Units created and managed by private sector (RPPNs) has gained increasing importance in the conservation effort, completing government conservation efforts. The amphibians are among the most diverse and threatened vertebrate group on the planet and, about 7.7% of its species are present in the remaining area of the Atlantic Forest Domain. In the last years, the population decline of these animals has become a notorious worldwide phenomenon whose main causes seems to be: global climate change, disease spread and, mainly, habitat loss. The amphibian’s biodiversity in Brazil is among the largest in the world and in the Atlantic Forest are registered 529 anuran species, found in all the phytophysiognomies of the biome. Legado das Águas are located at south of São Paulo state and have 31.000 ha, considered the largest area of Atlantic Forest under private protection in the country, representing about 1.5% of all remaining fragments of this biome. This work had as objective to present the anurofauna of Legado das Águas – Reserva Votorantim, SP, in order to describe the distribution pattern of the species and the habitat use in the forest reserve. Samplings were carried out between December 2016 and November 2017, in monthly campaigns, through three different methodologies: visual search, auditory search and tadpole’s collection. Samplings were performed during the day and night period, at ten permanent points, added with occasional records. A total of 44 species were recorded in 9 families: Brachycephalidae (3 spp.), Bufonidae (3 spp.), Craugastoridae (1 spp.), Hylidae (23 spp.), Hylodidae (3 spp.), Leptodactylidae (6 spp.), Microhylidae (1 spp.), Odontophrynidae (2 spp.) and Phyllomedusidae (2 spp.). Species richness remained higher in the rainy season and the species presented seasonal pattern. Most of the species registered are typical of forest environments and with arboreal habit, with vocalization sites in marshes and / or lakes. At one of the permanent sampling point were collected specimes belonging to the Hylodidae family for which identification was made through genetic sequencing. The molecular analysis identified two species: Crossodactylus caramaschii e C. werneri. The genetic distance of the sample collected for C. werneri was 1.90%, confirming the occurrence of the species in the studied area, increasing the distribution in 135 km to the south of its present distribution. The studied area presents an anuran high richness, but the period was not enough to register all the species with occurrence for the area, which point to the need of other methods combined to increase the possibility of the capture of species.
Amphibians of Legado das Águas-Reserva Votorantim, SP
Keywords: Comunidade de anuros; Distribuição sazonal; Uso de habitat; Mata Atlântica; Anurans community; Seasonal distribution; Use of habitat; Atlantic Rainforest; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA